Pengaruh Lifestyle, Discount, dan Promosi Gratis Ongkos Kirim terhadap Perilaku Impulse Buying Konsumen E-Commerce pada Mahasiswa Universitas Pendidikan Ganesha - Rohma, Antasya; Meitriana, Made Ary (Ekuitas: Jurnal Pendidikan Ekonomi, 2024)
The phenomenon of impulsive buying among consumers on e-commerce platforms based on unplanned purchases is a problem often faced by teenagers, especially students, who are unable to control their desires. Therefore, the author raised this research with the title The Influence of Lifestyle, Discounts and Free Shipping Promotions on the Impulse Buying Behavior of E-Commerce Consumers among Ganesha Education University Students. The type of research used in this research is quantitative research with a causal research design. The population used was all Ganesha Education University students with a sample of 130 e-commerce consumer respondents. The data collection method used in the research uses a questionnaire method. The data analysis technique used is multiple linear regression analysis, with data processing carried out using SPSS 25 for Windows computer software. The results of this study show that (1) there is a significant influence from lifestyle; (2) there is a significant effect of discounts; (3) there is a significant influence from the free shipping promotion; (4) there is a significant influence of lifestyle, discounts and free shipping promotions on the impulsive buying behavior of e-commerce consumers among Ganesha University of Education students.